ANALISIS HUBUNGAN DURASI DAN POSISI DUDUK TERHADAP RESIKO LOW BACK PAIN PADA KARYAWAN PUSKESMAS DINOYO - Rakhmad Rosadi; Sisilia Rabecha Rachel; Arys Hasta Baruna; Sri Sunaringsih Ika Wardojo (LPPM Universitas Abdurrab, 2023)
Background: Low Back Pain is one of the many problems that affect employees, which is characterized by acute and chronic low back pain that often spreads. This condition results in a decrease in employee productivity, even in their daily activities such as walking or lifting weights. Factors that play a role in this condition include age, gender, length of service, duration of work, work attitude, and work history. Research Objectives: To analyze whether there is a relationship between duration and sitting position with complaints of low back pain in employees. Research Methods: This study uses a survey design, where this study uses 2 instruments such as the Oswestry Disability Index (ODI) and the Numerical Rating Scale (NRS) to obtain information. This design also uses secondary data in the form of a number of journals obtained through databases such as Google Scholar and Pubmed in the 2010-2020 period. Conclusion: After analyzing, it was found that there was an influence between duration and a certain sitting position with a long duration of time on the risk of low back pain in employees at the Dinoyo Health Center.